Characteristics and neurological survival following intraoperative cardiac arrest in a Swiss University Hospital: a 7-year retrospective observational cohort study - Fuchs, Alexander; Franzmeier, Lea; Cheseaux-Carrupt, Marie; Kaempfer, Martina; Disma, Nicola; Pietsch, Urs; Huber, Markus; Riva, Thomas; Greif, Robert (Frontiers in Medicine, 2023)
Introduction Little is known about intraoperative cardiac arrest during anesthesia care. In particular, data on characteristics of cardiac arrest and neurological survival are scarce. Methods We conducted a single-center retrospective observational study evaluating anesthetic procedures from January 2015 until December 2021. We included patients with an intraoperative cardiac arrest and excluded cardiac arrest outside of the operating room. The primary outcome was the return of spontaneous circulation (ROSC). Secondary outcomes were sustained ROSC over 20 min, 30-day survival, and favorable neurological outcome according to Clinical Performance Category (CPC) 1 and 2. Results We screened 228,712 anesthetic procedures, 195 of which met inclusion criteria and were analyzed. The incidence of intraoperative cardiac arrest was 90 (CI 95% 78–103) in 100,000 procedures. The median age was 70.5 [60.0; 79.4] years, and two-thirds of patients (n = 135; 69.2%) were male. Most of these patients with cardiac arrest had ASA physical status IV (n = 83; 42.6%) or V (n = 47; 24.1%). Cardiac arrest occurred more frequently (n = 104; 53.1%) during emergency procedures than elective ones (n = 92; 46.9%). Initial rhythm was pre-dominantly non-shockable with pulseless electrical activity mostly. Most patients (n = 163/195, 83.6%; CI 95 77.6–88.5%) had at least one instance of ROSC. Sustained ROSC over 20 min was achieved in most patients with ROSC (n = 147/163; 90.2%). Of the 163 patients with ROSC, 111 (68.1%, CI 95 60.4–75.2%) remained alive after 30 days, and most (n = 90/111; 84.9%) had favorable neurological survival (CPC 1 and 2). Conclusion Intraoperative cardiac arrest is rare but is more likely in older patients, patients with ASA physical status ≥IV, cardiac and vascular surgery, and emergency procedures. Patients often present with pulseless electrical activity as the initial rhythm. ROSC can be achieved in most patients. Over half of the patients are alive after 30 days, most with favorable neurological outcomes, if treated immediately.